PENERAPAN NUMBER HEAD TOGETHER UNTUK MENINGKATKAN SIKAP SOSIAL SISWA PADA MATERI ELEKTROLIT DAN NON ELEKTROLIT DI SMA - Syailani Syailani (Vidya Karya, 2021)
The purpose of this study is to improve social attitudes such as honesty, cooperation, lending materials and care; and student learning outcomes in learning electrolyte and non-electrolyte solutions through the Numbered Head Together (NHT) model. This research is classroom action research. The subjects of this study were students of class X A 2 with 36 students—data collection techniques through non-test (observation, interviews, and documentation) and tests. The study results are as follows: (1) students' social attitudes have increased from cycle I to cycle II, both in the aspects of honesty, cooperation, lending materials, and caring. (2) classical learning outcomes also increased from cycle I to cycle II from 55% to 91%. It was concluded that the application of the NHT model could improve social attitudes and student learning outcomes.Keywords:  Electrolytes and Non Electrolytes; NHT; Social Attitudes Tujuan penelitian ini ialah meningkatkan sikap sosial seperti jujur, kerjasama, meminjam bahan dan peduli serta hasil belajar siswa pada pembelajaran larutan Elektrolit dan non Elektrolit melalui model Numbered Head  Together (NHT). Penelitian ini  merupakan penelitian tindakan kelas. Subjek penelitian ini ialah siswa kelas X A 2 sejumlah 36 siswa. Teknik pengumpulan data melalui non tes (observasi, wawancara, dan dokumentasi) dan tes. Adapun hasil penelitian sebagai berikut: (1) sikap sosial siswa mengalami peningkatan dari siklus I ke siklus II, baik pada aspek kejujuran, kerjasama, meminjamkan bahan, dan  peduli. (2) hasil belajar secara klasikal juga mengalami peningkatan dari siklus I ke siklus II dari nilai 55% menjadi 91%. Diperoleh simpulan bahwa penerapan model NHT dapat meningkatkan sikap sosial dan hasil belajar siswa.Kata kunci: Eletrolit dan Non Elektrolit; NHT; Sikap Sosial